2004
DOI: 10.1002/ejoc.200400458
|View full text |Cite
|
Sign up to set email alerts
|

Pyrano[2,3‐b]dioxanes through Bisacetalic Annulation of 2‐Ketosugars to Glycol

Abstract: The utility of 2‐ketohexosyl (“ulosyl”) bromides has been extended to the straightforward generation of cis‐fused pyrano[2,3‐b]dioxanes (1,4,5‐trioxadecalins) of type 11 and 13 by β‐specific and α‐selective glycosidation with glycol, and subsequent intramolecular hemiketalization. Mild basic conditions elicit highly stereoselective rearrangements to trioxadecalinones 22−25, representing the structurally and configurationally correct framework of steroidal natural products in which the sugar portion is doubly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Figure 2. The linkage geometry in various cardiac glycosides and in the antibiotic spectinomycin is invariably cis-cisoid-trans [7] Some recent model experiments on the silver carbonate promoted glycosidation of ulosyl bromide 5 with glycol [7] have shown that this step not only proceeds in a β-specific manner (5 Ǟ 6) but is spontaneously followed by an intramolecular hemiketalization from the upper face of the pyran ring (arrows in 6) to give the cis-annulated trioxadecalin 7, in which dipolar interactions between the pyranoid ring oxygen and the ketal-OH are minimized by their trans-diaxial disposition (Scheme 1). Scheme 1 As the molecular geometry of 7 corresponds to that of the pyrano-dioxane portion of the natural products 1Ϫ4, this ''ulosyl donor approach'' [8] offers the potential to provide a straightforward methodology towards their total syntheses, Ϫ especially, as none of the cardenolides has yet been synthesized and the strategies followed in two syntheses of spectinomycin [9] are unsuited for general application.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2. The linkage geometry in various cardiac glycosides and in the antibiotic spectinomycin is invariably cis-cisoid-trans [7] Some recent model experiments on the silver carbonate promoted glycosidation of ulosyl bromide 5 with glycol [7] have shown that this step not only proceeds in a β-specific manner (5 Ǟ 6) but is spontaneously followed by an intramolecular hemiketalization from the upper face of the pyran ring (arrows in 6) to give the cis-annulated trioxadecalin 7, in which dipolar interactions between the pyranoid ring oxygen and the ketal-OH are minimized by their trans-diaxial disposition (Scheme 1). Scheme 1 As the molecular geometry of 7 corresponds to that of the pyrano-dioxane portion of the natural products 1Ϫ4, this ''ulosyl donor approach'' [8] offers the potential to provide a straightforward methodology towards their total syntheses, Ϫ especially, as none of the cardenolides has yet been synthesized and the strategies followed in two syntheses of spectinomycin [9] are unsuited for general application.…”
Section: Introductionmentioning
confidence: 99%
“…The stereospecific conversion of the pyranodioxane 22 to a derivative with framework (S)-7 could also be achieved. 58 But in contrast to its (R)-configurated counterpart, the yield was lower and the reaction process less homogenous. For that reason, we also studied this stereoselective ring contraction of 22.…”
Section: Derivative With Spiroacetal Motif (S)-7mentioning
confidence: 98%
“…50,51 In the early 1980s, we developed a practical method for the conversion of the 2 literature-known d-glucose-derived 2-hydroxyglycal esters 9a 52,53 and 9b 54 into the corresponding ulosyl bromides 10a 55,56 and 10b. 57 We subsequently published 58 the glycosylation of 10a with the diol ethylene glycol to the bicyclic pyranodioxane (1,4,5-trioxa-cisdecaline) 11a. In the same paper, we also reported the ring contraction of 11a to the 2 1,6,9-tri-oxaspiro [4.5]decanes 14a and 15a together with consecutive bromide 16a and its dehalogenated derivative 17a.…”
Section: Synthesesmentioning
confidence: 99%
“…The pyran, dioxane, and cyclohexane rings are all in nearperfect chair conformations. Dihedral angles [8] relevant to the dioxanoid attachment: C2-O2-C2'-C3' À173.0, C3-O3-C1'-O5' 64.7, O3-C1'-C2'-C3' 172.7, O2'-C2'-C1'-O5' 172.3. …”
Section: Dedicated To Professor Andrµs Liptµk On the Occasion Of His mentioning
confidence: 99%
“…Thus for annulation of their sugar portion, alternatives that are capable of reaching this objective more directly became imperative. On the basis of our previous studies on the extension of the "ulosyl donor approach" [7] to glycol and (R,R)-1,2-cyclohexanediol, which smoothly led to cis-fused pyranodioxanes [8] and to pyran-dioxane-cyclohexane tricycles [9] in cis,cisoid,-trans fusion, we inferred that the d-glucose-derived 2-ketohexosyl donors 10 and 11 would be particularly well-adjusted for targeting natural products with annulated sugar components. The donors not only contain the 2-carbonyl function, which is essential for generation of the cyclohemiacetal linkage, but in the case of 10, an enol-ester-protected carbonyl at C-3 is also present thereby closely matching the tricarbonyl sugar units in 3, 6, and 7.…”
Section: Dedicated To Professor Andrµs Liptµk On the Occasion Of His mentioning
confidence: 99%